Mengidentifikasi Permasalahan Pembelajaran IPAS Pada Kelas VI di SD Negeri 95/I OLAK Muara Bulian - Khoirunnisa; Raihan Andri Setiawan; Nurzat Ali; Rayhan Febriansyah Putra; M. Miftahul Ulum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning Natural and Social Sciences (IPAS) in Elementary School is an effort to provide knowledge and experience to students to help them see and understand social life and natural phenomena around them. However, in reality, various problems are still found that hinder the learning process. In this study, the aim is to identify what problems in the learning of IPAS exist in grade VI at SDN 95/I OLAK. The research method used is a descriptive qualitative method through observations of the learning process of IPAS in Grade VI. The results of the study indicate that the problems found during the observation are such as the lack of teaching media and learning resources, low interest in learning in students, and challenges for teachers in managing the class and developing effective and interesting learning strategies.